Classical Music Therapy on Decreasing Auditory Hallucinations for Mental Disorder Patients - Sri Angriani; Rusni Mato; Rahman Rahman (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Auditory hallucinations are one of the symptoms of mental disorders in which individuals experience sensory-perceptual changes that need to get treatment as soon as possible. To overcome the problem of auditory hallucinations, this can be done through music therapy. The aim of the study was to determine the effect of classical music therapy on reducing auditory hallucinations in patients with mental disorders. The research method used a quasi-experimental pre-post test. The sample in this study were 30 people. The results of statistical analysis using the paired t-test showed a p-value of 0,000, which means that there was an effectiveness of classical music therapy in reducing signs and symptoms of auditory hallucinations. The conclusion is that there is an effect of the effectiveness of classical music therapy on the reduction of signs and symptoms in patients with auditory hallucinations at the Dadi Mental Hospital Makassar.